(3GdcfR GdeOahf hGdadc GdeTMhfs - (3jhfS GdeGdcjs ((3CMeO eci s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO , abO LeYJ eG JVefg gPG GdeLehY ef ahGFO hZjQgG djJfRg HgG GdfGXQ hjfTQM HQDjJgG GdNGWQ hSejJg GdcfR GdeOahf hGdadc GdeTMhf s
(3BNQgG (B:s
(3jQGe SQc efi , hUhf MHc afi , hbUO VOc Cfi , jbGd Pdc Yfi Je cJGH GdcfR GdeOahf hGdadc GdeTMhf s
(3GdeYQha Cf GdcJGH hefShHkG Edi GdSjhWi adjbGQf HGdWHYs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1519s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdCOHs